Transformasi Tatanan Sosial Masyarakat dalam Proses Islamisasi Kerajaan Sintang Abad 16–18 - Mukhammad Yafi Aditiya (Medan Resource Center, 2025)
This study aims to analyze the transformation of the social order in the Sintang Kingdom during the process of Islamization. Employing a qualitative-analytical method with a historical approach, the research applies the stages of heuristics, source criticism, interpretation, and historiography to examine historical sources obtained through library research. The findings reveal that Islamization in the Sintang Kingdom constituted a gradual process of cultural and religious adaptation rather than an abrupt replacement of the existing social system. This transformation was reflected in the integration of Islamic values into customary law, the adoption of Islamic principles in marriage practices, the reorientation of political legitimacy and royal leadership, and the expansion of Islamic religious institutions that reshaped patterns of social interaction. Despite these changes, several local customs continued to coexist with Islamic traditions, demonstrating a process of cultural accommodation. This study contributes to the historiography of Islam in West Kalimantan by showing that Islamization in the Sintang Kingdom represented a process of social transformation characterized by negotiation and adaptation between local traditions and Islamic values, rather than a simple religious conversion.